1993
DOI: 10.1007/bf02011953
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric sedation: short-term effects

Abstract: A prospective investigation on the short-term effects of various sedation regimens on 549 nonhospitalized magnetic resonance (MR) patients was performed. The drugs evaluated were chloral hydrate, pentobarbital, midazolam, and diazepam (fentanyl was used for enhancement after any of these drugs). The overall safety and efficacy were quite good with all the regimens. Overall, 84% of children slept less than 8 h after the examination, 90% were drowsy and/or unsteady for less than 8 h after they awoke, and 97% res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…I). This idea may have led to the establishment of low age limits for the use of oral chloral hydrate in the paediatric population, as reported and recommended in the literature (6,(8)(9)(10). However, in our series, failure rates were very low (<5%) for children under 36 months old, but still low (C75%) for children up to 7 years old.…”
Section: Go-20 Psupporting
confidence: 54%
“…I). This idea may have led to the establishment of low age limits for the use of oral chloral hydrate in the paediatric population, as reported and recommended in the literature (6,(8)(9)(10). However, in our series, failure rates were very low (<5%) for children under 36 months old, but still low (C75%) for children up to 7 years old.…”
Section: Go-20 Psupporting
confidence: 54%
“…However, Slovis et al . (8) found that 11 and 19% of children >8 and <8 years of age, respectively, slept more than 8 h, and 37.5% of those >8 years of age were hyperactive following PB sedation for MRI. Furthermore, these investigators reported that 3% of children who received i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphoria, anxiety, and agitation have been associated with the use of several sedative/hypnotic agents including the phenothiazines, benzodiazepines, barbiturates, as well as ketamine. 7,[12][13][14][15] Slovis et al 7 reported a higher incidence of hyperactivity with the use of pentobarbital (3%) compared with other sedatives. Depression of inhibitory centers in the central nervous system has been suggested as the mechanism for barbiturate induced paradoxical excitement.…”
Section: Discussionmentioning
confidence: 99%